Answer:
The simplified expression is ![\frac{10}{3 a^2 b}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B3%20a%5E2%20b%7D)
Step-by-step explanation:
The given expression is:
![\frac{15b}{4} * \frac{8}{9a^2 b^2}](https://tex.z-dn.net/?f=%5Cfrac%7B15b%7D%7B4%7D%20%2A%20%5Cfrac%7B8%7D%7B9a%5E2%20b%5E2%7D)
Multiply the items in the numerator together ( 15b * 8 = 120 b). Also multiply the items in the denominator together ( 4 * 9a²b² = 36a²b²). The expression thus becomes:
![= \frac{120b}{36 a^2 b^2} \\\\](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B120b%7D%7B36%20a%5E2%20b%5E2%7D%20%5C%5C%5C%5C)
Divide both the numerator and the denominator by 12b:
![= \frac{120b /12b}{36 a^2 b^2/12b}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B120b%20%2F12b%7D%7B36%20a%5E2%20b%5E2%2F12b%7D)
The expression finally becomes:
![= \frac{10}{3 a^2 b}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B10%7D%7B3%20a%5E2%20b%7D)
Right scalene triangle, because each side is a different length.
The surface 5 cm, and the length is 10 cm
Answer:
2 places after the decimal point.
Step-by-step explanation:
Here is the answer for prove that cos theta by 1 minus tan theta + sin theta by 1 minus cot theta equal to sin theta + cos theta